2021
DOI: 10.1038/s41577-021-00544-9
|View full text |Cite
|
Sign up to set email alerts
|

Concerns about SARS-CoV-2 evolution should not hold back efforts to expand vaccination

Abstract: When vaccines are in limited supply, expanding the number of people who receive some vaccine, such as by halving doses or increasing the interval between doses, can reduce disease and mortality compared with concentrating available vaccine doses in a subset of the population. A corollary of such dose-sparing strategies is that the vaccinated individuals may have less protective immunity. Concerns have been raised that expanding the fraction of the population with partial immunity to SARS-CoV-2 could increase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
124
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(134 citation statements)
references
References 70 publications
2
124
0
1
Order By: Relevance
“…With the emergence of several SARS-CoV-2 variants, it remains uncertain whether vaccines and antibody-based therapies will lose efficacy 17 . Cell-culture based studies have shown that several of the mutations in variant strains, especially those at positions 452 and 484, result in reduced neutralization by antibodies derived from infected or vaccinated individuals [1][2][3]18,19 .…”
Section: Therapeutic Efficacy Against Variantsmentioning
confidence: 99%
“…With the emergence of several SARS-CoV-2 variants, it remains uncertain whether vaccines and antibody-based therapies will lose efficacy 17 . Cell-culture based studies have shown that several of the mutations in variant strains, especially those at positions 452 and 484, result in reduced neutralization by antibodies derived from infected or vaccinated individuals [1][2][3]18,19 .…”
Section: Therapeutic Efficacy Against Variantsmentioning
confidence: 99%
“…With the current limitations on vaccine supply, many nations are asking to what degree the recommended dosing regimen of COVID-19 vaccines could be altered (dose-sparing strategies) without impacting effectiveness. 180 For instance, the trials of the Oxford-AstraZeneca vaccine concluded that a longer gap between doses (2-3 months) led to greater immune responses. 115,181 Andrew Pollard, the head of the Oxford Vaccine Group and chief investigator into the trial of this vaccine, claimed: ''a longer gap between vaccine doses leads to a better immune response, with the second dose causing a better boost.''…”
Section: Remaining Concerns Relevant To Covid-19 Vaccine Development and Concluding Remarksmentioning
confidence: 99%
“…Although insufficient selective pressure due to a lower dose theoretically increases the likelihood that a resistant viral strain emerges, so too does actively choosing not to maximise vaccine availability. 9 Real-world data support an activist approach to vaccine dosing 4 , 5 and, to our knowledge, no vaccine-resistant strains have emerged in the UK. We all must acknowledge that even in the best of pandemic circumstances—infinite vaccine supply allowing for strict adherence to dosing guidance from randomised controlled trials—the emergence of a vaccine-resistant viral strain is a known unknown.…”
mentioning
confidence: 92%